Penyuluhan Mengenai Beberapa Teknik Untuk Menginduksi Pembungaan Pada Tanaman Mucuna Bracteata Di Desa Kampung Padang Kecamatan Pangkata Kabupaten Labuhanbatu - Sitanggang, Kamsia Dorliana; Saragih, Siti Hartati Yusida; Rizal , Khairul (HIMPUNAN DOSEN GEMILANG INDONESIA, 2023)
Most of Kampung Padang resident is a farmer especially as a oil palm and rubber farmer. In the cultivation of oil palm and rubber, there are still a few villagers from Kampung Padang who plant Mucuna between plants as a ground cover crop or Legume Cover Crop, even though Mucuna has many benefits, especially for suppressing weed growth and improving soil chemical properties. The difficulty of obtaining seeds makes people rarely use Mucuna. Some techniques that can be done to induce flowering in plants are using a growth regulator (ZPT) paclobutrazol. Several research results regarding the use of paclobutrazol have succeeded in shortening the length of plant tendrils. Other techniques that can be used to induce flowering in plants are providing water stress, ringing the plants, and pruning the roots of the plants. The response from the people of the Padang village population was very enthusiastic, seen from the many people who asked questions during the event.